Pengaruh Pola Asuh Orang Tua terhadap Agresivitas Anak Usia 5-6 Tahun di KB PAUD Mekar Sari Kundi - Puput, Puput (ICEJ : Islamic Childhood Education Journal, 2025)
This study was motivated by the high aggressive behavior in group B children at KB PAUD Mekar Sari Kundi. This behavior is very detrimental to their development as well as the safety and comfort of others. The impact of aggressive behavior not only affects children's function in emotional and behavioral development, but it also affects their academic achievement, social interactions with peers and teachers. The influence of parenting patterns is very important for early childhood because early childhood education determines the growth and development of children to the next stage. This study aims to determine the effect of parenting patterns on the aggressiveness of group B children at KB PAUD Mekar Sari Kundi. This study uses a quantitative approach with an ex-post facto research method. The study population was all group B children at KB PAUD Mekar Sari Kundi, totaling 40 people with a sampling technique using saturated sampling. The data collection techniques used were questionnaires and documentation. The validity test used the Person Product Moment formula test and the reliability test used the Croncbach's Alpha formula. The data analysis technique used statistical tests, namely the normality test, linearity test, and hypothesis test using the Simple Linear Regression test. Data analysis was carried out using SPSS software version 22. Based on the results of the hypothesis test, it is known that the Simple Linear Regression value of parenting patterns on child aggression is 187,400 with a Sig. (2-tailed) value of 0.000. Compared to the significance level of 0.05 (5%), the Sig. (2-tailed) value is smaller than 0.05 (5%). This means that Ho is rejected and Ha is accepted. The conclusion is that there is an influence of parenting patterns on the aggressiveness of children aged 5-6 years at KB PAUD Mekar Sari Kundi. The test is also strengthened by looking at the value of the coefficient of determination (R Square) where the value is 0.831. This means that the influence of parenting patterns on child aggression is 83.1% and only 17% is influenced by other factors.